Employment and Income Shock During COVID-19 Lockdown in a Metropolitan city in India. Issue 2 (March 2023) - Dev, Pritha; Unni, Jeemol; Vijayalakshmi, Akshaya
The COVID-19 crisis had a harsher impact on women globally, as they were disproportionately represented in sectors offering low wages, few benefits and least secure jobs. We examined the economic impact of loss of employment and incomes on workers in relatively low income households during and after the first stringent lockdown—April to June 2020—in Ahmedabad, Gujarat. We analyse employment impact using a logistic regression and impact on incomes using a Fixed Effect OLS regression. We find that the impact on women workers was greater in terms of loss of employment and income. Women had clearly not resumed work at the same rate as men after lockdown was eased. We address the specific question, 'why were women less likely to resume work after the shock of lockdown?' We found that care responsibilities did not explain later resumption of work, but the place of work did. In addition we address the question 'which segments of workers suffered greater income loss?' We analyse these questions for wage and self-employed workers and by prominent occupations in the sample. We find that while wage-employed workers resumed work later, they suffered less income loss than the self-employed. We attempt to explain this paradox. JEL Codes: J4, J46, J39, O17, R23